ANALYSIS OF THE EFFECTIVENESS OF ISLAMIC BOARDING SCHOOL-BASED LEARNING IN IMPROVING UNDERSTANDING OF ISLAMIC TEACHINGS - Ahmad Jauhari; Moh. Ali (RADJA PUBLIKA, 2026)
This study aims to analyze the effectiveness of Islamic boarding school-based learning in improving the understanding of Islamic teachings among students (students). This qualitative research was conducted using a case study approach in one Islamic boarding school. The research sample consisted of 20 students who had participated in the Islamic boarding school-based learning program for 6 months. The results of the study indicate that Islamic boarding school-based learning is effective in improving the understanding of Islamic teachings among students. Students who participated in the Islamic boarding school-based learning program showed a significant increase in their understanding of Islamic teachings, especially in terms of understanding the principles of Islamic teachings and being able to apply Islamic teachings in their daily lives. In addition, the study also found that factors influencing the effectiveness of Islamic boarding school-based learning include the quality of the teachers, the students' motivation, and support from family and community. The conclusion of this study is that Islamic boarding school-based learning can be an effective alternative in improving the understanding of Islamic teachings among students. Therefore, the government and educational institutions need to prioritize Islamic boarding school-based learning to improve the quality of religious education in Indonesia.